Multivalent Batteries—Prospects for High Energy Density: Ca Batteries - Monti, Damien; Ponrouch, Alexandre; Araujo, Rafael B.; Barde, Fanny; Johansson, Patrik; Palacín, M. Rosa (Frontiers in Chemistry, 2019)
Batteries based on Ca hold the promise to leapfrog ahead regarding increases in energy densities and are especially attractive as Ca is the 5th most abundant element in the Earth's crust. The viability of Ca metal anodes has recently been shown by approaches that either use wide potential window electrolytes at moderately elevated temperatures or THF-based electrolytes at room temperature. This paper provides realistic estimates of the practical energy densities for Ca-based rechargeable batteries at the cell level, calculated using open source models for several concepts. The results from the Ca metal anode batteries indicate that doubled or even tripled energy density as compared to the state-of-the-art Li-ion batteries is viable if a practical proof-of-concept can be achieved.